THE REPRESENTATION OF WOMEN CHARACTERS IN THE MOVIE THE BREADWINNER - Deta Maria Sri Darta; Diah Kristina (Sanata Dharma University, 2018)
This article would like to present how women were defined in the movie, both by male and female characters. Mills (1998) provides a tool to help the readers understanding the style of a writer through her choices of words, sentences, and even in the discourse level. A novel based movie which won and was nominated in several awards, The Breadwinner, was full of portrayal of women in the setting of Afghanistan under the Taliban rule. The tragic story was beautifully wrapped under the animated movie produced to show the real picture towards the world. The data are in the form of words, sentences and discourse spoken by male and female characters that represent the depiction of women. The data obtained are examined with the view of Sara Mills theory. It is found that in the movie, the women are represented as two opposing aspects: women representation as an object of man domination,and women as the subject who is able to speak out her mind and to decide independently.